Biomechanical determinants of cross-country skiing performance: A systematic review - Zoppirolli, C.; Hébert-Losier, K.; Holmberg, H. C.; Pellegrini, B. (Journal of Sports Sciences, 2020)
Cross-country skiing is a complex endurance sport requiring technical skills, in addition to considerable physiological and tactical abilities. This review aims to identify biomechanical factors that influence the performance of cross-country skiers. Four electronic databases were searched systematically for original articles in peer-reviewed journals addressing the relationship between biomechanical factors (including kinematics, kinetics, and muscle activation) and performance while skiing on snow or roller skiing. Of the 46 articles included, 22 focused exclusively on the classical technique, 18 on the skating technique, and six on both. The indicators of performance were: results from actual or simulated races (9 articles); speed on specific tracts (6 articles); maximal or peak speed (11 articles); skiing economy or efficiency (11 articles); and grouping on the basis of performance or level of skill (12 articles). The main findings were that i) cycle length, most often considered as a major determinant of skiing speed, is also related to skiing economy and level of performance; ii) higher cycle rate related with maximal speed capacity, while self-selected cycle rate improves skiing economy at sub-maximal speeds; iii) cross-country skiing performance appears to be improved by joint, whole-body, ski, and pole kinematics that promote forward propulsion while minimizing unnecessary movement.